2017
DOI: 10.4317/medoral.21864
|View full text |Cite
|
Sign up to set email alerts
|

Dental management of pediatric patients affected by pulmonary atresia with ventricular septal defect: A scoping review

Abstract: BackgroundCongenital Heart Diseases (CHD) involves a wide range of pathological conditions, such as Pulmonary Atresia with Ventricle Septal Defect (PA/VSD). This disorder leads to the systemic circulation of oxygen-poor blood (cyanosis), with associated features and consequences in the oral cavity.Material and MethodsUsing scoping review methodology for screening and article selection, the primary objectives of this paper were as follows: first, to pose a research question; second, to identify relevant studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 27 publications
(65 reference statements)
0
18
1
6
Order By: Relevance
“…Again, given the use of different indices, caution is also required when comparing results for plaque and gingivitis among different reports. In the present study, gingivitis and plaque were found to be highly prevalent among children with CHDs, and the percentages were much higher than in previous studies (1). Fifteen of the cases in the present study were found to have gingival hyperplasia.…”
Section: Oral Manifestations Concerning Marginal Periodontiumcontrasting
confidence: 73%
See 4 more Smart Citations
“…Again, given the use of different indices, caution is also required when comparing results for plaque and gingivitis among different reports. In the present study, gingivitis and plaque were found to be highly prevalent among children with CHDs, and the percentages were much higher than in previous studies (1). Fifteen of the cases in the present study were found to have gingival hyperplasia.…”
Section: Oral Manifestations Concerning Marginal Periodontiumcontrasting
confidence: 73%
“…As a result of progress in medical procedures and the use of prosthetic materials for correction of CHDs, the prognosis for these patients has improved. Children with CHDs now have a greater life expectancy, and many of them reach adulthood (1,27). Nevertheless, these children remain at a higher risk than healthy children of developing serious and potentially fatal heart-related infections, such as infective endocarditis (1,27).…”
Section: Risk Of Systemic Complications Due To Oral Disease In Childrmentioning
confidence: 99%
See 3 more Smart Citations